PENGETAHUAN PEMANFAATAN TUMBUHAN SECARA TRADISIONAL DI SUKU KULAWI, SULAWESI TENGAH - Hurria, Hurria (BUANA SAINS, 2023)
Knowledge of the traditional use of plants has been passed down from generation to generation by the Kulawi ethnic community in Salua village, Central Sulawesi. In this study, we document community knowledge about the effect of plants as medicinal plants, traditional ceremonies, food/drinks, and building materials. Based on the results of interviews and exploration, the plant that collected 25 species was found with local names, parts used, and how to use them. A total of 18 species can used as medicinal plants, five species for food/drink, one species for building materials, and three for traditional ceremonies. Our study recommends ex-situ management of natural resources so that plants can used sustainably.